Composite hydrogel based on biological template induction and dual-network synergistic enhancement, preparation method of composite hydrogel and application of composite hydrogel in flexible sensor

By in situ polymerizing PEDOT:PSS@HEC and PAM on hydroxyethyl cellulose, the dual network hydrogels are solved, and the dispersion and mechanical properties of conductive polymers in flexible sensing materials are achieved, achieving high sensitivity and fast response sensing effects.

CN120504851APending Publication Date: 2025-08-19INST OF CHEM IND OF FOREST PROD CHINESE ACAD OF FORESTRY
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202510643015.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-05-19
Publication Date
2025-08-19

AI Technical Summary

Technical Problem

In existing flexible sensing materials, conductive polymers are difficult to disperse uniformly and mechanical and conductive properties are difficult to improve synergistically. The traditional composite methods have the problem of performance inversion.

Method used

Hydroxyethyl cellulose (HEC) was used as a biological template to synthesize PEDOT:PSS@HEC composite material through in-situ polymerization, and a dual network hydrogel was constructed with polyacrylamide (PAM) to form a network structure that is both rigid and flexible.

Benefits of technology

It realizes high sensing sensitivity, wide detection range and fast response of conductive hydrogels, and is suitable for flexible sensors to provide real-time electrochemical signal feedback.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN120504851A_ABST
    Figure CN120504851A_ABST
Patent Text Reader

Abstract

The invention discloses composite hydrogel based on biological template induction and dual-network synergistic enhancement, a preparation method of the composite hydrogel and application of the composite hydrogel in a flexible sensor, and the preparation method of the composite hydrogel comprises the following steps: dissolving hydroxyethyl cellulose in a solvent to obtain a homogeneous dissolving solution; 3, 4-ethylenedioxythiophene and polystyrolsulfon acid are added into the dissolving solution, an initiator and an oxidizing agent are added, the pH of the system is adjusted to be acidic with sulfuric acid, EDOT is fully polymerized till the reaction is complete, and HEC anchored composite conductive polymer dispersion liquid is obtained; the preparation method comprises the following steps: preparing a pre-polymerized solution of acrylamide, uniformly mixing the pre-polymerized solution of acrylamide and the dispersion solution containing the composite conductive polymer, and carrying out thermal-initiated free radical polymerization to obtain a target product. The composite hydrogel is excellent in mechanical property, and a packaged sensor is wide in detection range, high in sensitivity, rapid in response and good in stability and can provide real-time and efficient electrochemical signal change feedback for physiological activities of a human body.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the field of high-value utilization of biomass resources and flexible sensing, and specifically relates to a composite hydrogel based on biological template induction and double network synergistic enhancement, a preparation method thereof, and application in flexible sensors. Background Art

[0002] The rapid development of flexible electronics is reshaping the boundaries of human-computer interaction. According to IDC's forecast, the global wearable device market will exceed $80 billion by 2025. Flexible sensing technology, as a core enabler, places revolutionary demands on material systems. Traditional rigid sensors, lacking the mechanical compliance, interface adaptability, and environmental adaptability required in emerging fields such as smart healthcare and sports monitoring, have proven difficult to meet. This has prompted researchers to turn their attention to biomimetic conductive hydrogels. Their unique ionic / electronic dual conduction mechanism, tissue-like mechanical properties, and stimuli-responsive behavior provide an ideal platform for building a new generation of flexible sensing systems.

[0003] Among the many conductive polymers, poly(3,4-ethylenedioxythiophene) (PEDOT) and its derivatives have become star materials in the field of flexible electronics due to their outstanding conductivity, environmental stability and solution processability. However, the inherent brittleness and poor interfacial adhesion of poly(3,4-ethylenedioxythiophene) and polystyrene sulfonic acid (PSS) composite films seriously restrict their application in dynamic sensing scenarios. Recent studies have mostly used nanocomposite strategies to improve their mechanical properties, but often at the expense of conductivity. For example, although the polyvinyl alcohol (PVA) composite system can improve its toughness, it causes the conductivity to drop by 2-3 orders of magnitude. This trade-off in performance highlights the limitations of traditional composite methods, and there is an urgent need to develop new structural design strategies to achieve conductive-mechanical synergistic enhancement.

[0004] Hydrogels, as soft materials with three-dimensional network structures, have become a research hotspot in the field of flexible sensing due to their exceptional flexibility and deformability. Unlike traditional rigid materials, hydrogels can be endowed with a variety of functional properties through molecular design, offering unique advantages in the construction of biomimetic sensing systems. Developing green electronic materials derived from biomass resources offers dual benefits in response to the "dual carbon" strategy. Hydroxyethyl cellulose (HEC), an etherified derivative of lignocellulose, possesses a hydroxyl network capable of forming dynamic physical crosslinks, while its highly substituted ethoxy side chains impart the ability to form hydrophobic microdomains. This combination of rigidity and flexibility provides an ideal platform for stress dissipation. Compared to petroleum-based polymers, HEC's renewability and biodegradability significantly reduce its lifecycle environmental impact. Life cycle assessments show that its production process consumes far less fossil energy than polyurethane. Recent studies have confirmed the unique advantages of cellulose-based conductive composites in interface engineering. For example, the nanocellulose template effect can be used to orient PEDOT chains, but the cumbersome pretreatment process has limited its large-scale application. This suggests that the synergistic mechanism between biomass materials and conductive polymers needs to be reconstructed at the molecular interaction level rather than a simple physical compound. Summary of the Invention

[0005] To address the challenges of uniform dispersion of conductive polymers in existing flexible sensing materials and the difficulty in synergistically enhancing their mechanical and electrical properties, the present invention provides a composite hydrogel based on bio-template induction and dual-network synergistic enhancement, its preparation method, and its application in flexible sensors. The present invention synthesizes the conductive polymer PEDOT:PSS@HEC through in situ polymerization on the surface of hydroxyethyl cellulose (HEC). A composite conductive hydrogel is successfully prepared using PEDOT:PSS@HEC and polyacrylamide (PAM) as the main components of the polymer network. The prepared hydrogel, applied to flexible sensors, exhibits a wide detection range (1060%), high sensitivity (GF = 7.35), fast response (55ms and 660ms), and good stability, effectively providing real-time and efficient feedback of electrochemical signal changes in human physiological activities.

[0006] The technical solution adopted in the present invention is:

[0007] The first object of the present invention is to provide a method for preparing a composite conductive hydrogel based on biological template induction and double network synergistic enhancement, comprising the following steps:

[0008] Preparation of a HEC-templated PEDOT:PSS@HEC composite material: Hydroxyethyl cellulose and water are thoroughly mixed to obtain a homogeneous solution; conductive polymer monomers 3,4-ethylenedioxythiophene (EDOT) and polystyrene sulfonic acid are added to the solution, and the pH of the system is adjusted to 2. Considering the structure of polystyrene sulfonic acid, sulfuric acid is used to adjust the pH to avoid the introduction of other acid ions. An ice-water bath is used to control the temperature of the system to obtain a suitable reaction system for monomer polymerization; an initiator and an oxidant are added to the system to initiate the polymerization reaction and ultimately obtain a composite conductive polymer dispersion. The mass fraction of hydroxyethyl cellulose in the solution is 0.25wt% to 1.5wt%, preferably 0.75wt%. The abundant hydroxyl groups in the hydroxyethyl cellulose can anchor the 3,4-ethylenedioxythiophene monomer and further induce its polymerization. The initiator used to prepare the conductive polymer dispersion is ammonium persulfate, and the oxidant is ferric chloride.

[0009] Preparation of PEDOT:PSS@HEC / PAM composite hydrogel: acrylamide monomer is dissolved in water, and an initiator and a cross-linking agent are added in sequence, and the reaction is carried out at room temperature to obtain an acrylamide prepolymer solution; a PEDOT:PSS@HEC conductive polymer dispersion is added to the acrylamide prepolymer solution and mixed evenly, and a hydrogel is obtained by thermally initiating free radical polymerization, wherein the concentration of acrylamide monomer in the acrylamide prepolymer solution is 30wt%, the storage temperature of the acrylamide prepolymer solution after synthesis is a low temperature environment below 8°C, the reaction temperature of the gelation process is 70°C, and the reaction time is 2 hours; the initiator used to prepare the acrylamide prepolymer solution is ammonium persulfate, and the cross-linking agent is N,N'-methylenebisacrylamide.

[0010] The second object of the present invention is to provide a composite hydrogel based on biological template induction and double network synergistic enhancement, wherein the composite hydrogel is prepared by the preparation method described in the first object above.

[0011] The third object of the present invention is to provide an application of the composite hydrogel based on biological template induction and double network synergistic enhancement as described in the second object in a flexible sensor.

[0012] Compared with the prior art, the present invention has at least the following beneficial effects:

[0013] The present invention uses the skeleton of hydroxyethyl cellulose (HEC) as a template, and its abundant hydroxyl groups anchor EDOT monomers through hydrogen bonding, inducing their directional polymerization within the confined microenvironment of the HEC molecular chain;

[0014] The present invention introduces polystyrene sulfonic acid (PSS) as an auxiliary functional medium and uses sulfuric acid to adjust the pH value of the system. On the one hand, the π-π interaction between the sulfonic acid group and EDOT promotes the orderly stacking of molecular chains, and on the other hand, the electrostatic repulsion effect inhibits the agglomeration of PEDOT nanofibers.

[0015] This invention introduces acrylamide (AM) into the resulting PEDOT:PSS@HEC conductive composite to construct a secondary network. Free radical polymerization creates a covalently cross-linked PAM rigid backbone, ultimately resulting in a network structure that is both rigid and flexible. Zeta potential and AFM analysis confirm that when the HEC content is optimized to 0.75wt%, the PEDOT:PSS@HEC exhibits high dispersibility. The resulting PEDOT:PSS@HEC / PAM hydrogel material simultaneously exhibits a high sensing GF value, a wide sensing range, and rapid responsiveness, breaking through the performance inversion dilemma of traditional composite materials. BRIEF DESCRIPTION OF THE DRAWINGS

[0016] Figure 1 This is a flow chart for the preparation of the conductive polymer PEDOT:PSS@HEC and the hydrogel PEDOT:PSS@HEC / PAM provided in Example 1 of the present invention.

[0017] Figure 2 The mechanical properties test results of PEDOT:PSS@HEC / PAM and PAM hydrogels provided in Example 1, Example 2 and Comparative Example 1 of the present invention.

[0018] Figure 3 These are morphology images of PEDOT:PSS@HEC synthesized at different HEC concentrations (0, 0.75, and 1.5 wt %) provided in Example 1, Example 2, and Comparative Example 2 of the present invention.

[0019] Figure 4 The gauge coefficient and cyclic stability test results under different strains of the PEDOT:PSS@HEC / PAM hydrogel sensor provided in Example 1 of the present invention.

[0020] Figure 5 The response time and anti-fatigue performance results of PEDOT:PSS@HEC / PAM provided in Example 1 of the present invention.

[0021] Figure 6 This is the human body sensing performance result of PEDOT:PSS@HEC / PAM provided in Example 1 of the present invention.

[0022] Figure 7 These are the human electrocardiogram and electromyography signal test results of the PEDOT:PSS@HEC / PAM provided in Example 1 of the present invention. DETAILED DESCRIPTION

[0023] The present invention will be further described below with reference to the embodiments so that those skilled in the art can better understand the present invention and implement it, but the embodiments are not intended to limit the present invention.

[0024] In addition, unless otherwise specified, the preparation processes in the following examples are conventional means in the prior art in the field, and therefore, they are not described in detail.

[0025] Example 1

[0026] refer to Figure 1 A method for preparing a composite hydrogel based on biological template induction and double network synergistic enhancement comprises the following steps:

[0027] (1) Preparation of conductive polymer dispersion: Hydroxyethyl cellulose was dissolved in water to prepare a 0.75 wt% HEC solution. 3,4-ethylenedioxythiophene (EDOT) monomer and polystyrene sulfonic acid (PSS) were slowly added to the HEC solution with stirring, and ultrasonic dispersion was performed to form a homogeneous mixture. The mass ratio of EDOT to PSS in the mixture was 1:2.5, and the total mass fraction of the two was 1.5 wt% of the mixture. The pH value of the system was adjusted to 2 with sulfuric acid, and then the initiator ammonium persulfate (APS) and the oxidant ferric chloride (FeCl3) were added. The molar ratio of the initiator ammonium persulfate to the monomer 3,4-ethylenedioxythiophene was 1.17:1, and the molar ratio of the oxidant ferric chloride to the monomer 3,4-ethylenedioxythiophene was 0.01:1. The mixture was stirred gently in an ice-water bath to allow EDOT to fully polymerize until the reaction was complete, and finally a HEC-anchored conductive polymer (PEDOT:PSS@HEC) dispersion was obtained.

[0028] (2) Preparation of acrylamide prepolymer solution and preparation of conductive hydrogel: A low-temperature prepolymerization method was used to form a prepolymer network of acrylamide (AM). AM was dissolved in water to obtain a solution with a mass fraction of 30 wt%. Subsequently, the initiator ammonium persulfate and the crosslinker N,N'-methylenebisacrylamide were added. The addition amounts of the crosslinker N,N'-methylenebisacrylamide and the initiator ammonium persulfate were 0.17 wt% and 0.15 wt% of the mass of the AM monomer, respectively. The reaction was carried out at room temperature for 1 hour to form a prepolymer solution with adjustable crosslinking density. The PEDOT:PSS@HEC dispersion was mixed with the AM prepolymer solution in a volume ratio of 1:7, and the two-phase uniform dispersion was achieved by vortex mixing and ultrasonic treatment. The mixed system was added to a homemade hydrogel mold and thermally initiated polymerization at a temperature of 70 ° C and a reaction time of 2 hours to finally form a covalently crosslinked polyacrylamide (PAM) network. At the same time, the physically crosslinked composite conductive polymer network was uniformly embedded in it, namely, a double network hydrogel (PEDOT:PSS@HEC / PAM). By Figure 2 and Figure 3It can be found that the conductive polymer obtained in Example 1 has good uniformity, and the hydrogel prepared based on this conductive polymer also exhibits good mechanical properties.

[0029] (3) Hydrogel encapsulation and sensing performance testing: The prepared hydrogel was cut into appropriate sizes and encapsulated with VHB transparent tape to ensure that the hydrogel was isolated from the external environment. The encapsulated hydrogel was used as a sensing element and connected to a signal acquisition system. Its resistance change under different strains was tested to evaluate its sensing performance.

[0030] Example 2

[0031] A method for preparing a composite hydrogel based on biological template induction and double network synergistic enhancement comprises the following steps:

[0032] (1) Preparation of conductive polymer dispersion: Hydroxyethyl cellulose was dissolved in water to prepare a 1.5 wt% HEC solution. 3,4-ethylenedioxythiophene (EDOT) monomer and polystyrene sulfonic acid (PSS) were slowly added to the HEC solution with stirring, and ultrasonic dispersion was performed to form a homogeneous mixture. The mass ratio of EDOT to PSS in the mixture was 1:2.5, and the total mass fraction of the two was 1.5 wt% of the mixture. The pH value of the system was adjusted to 2 with sulfuric acid, and then the initiator ammonium persulfate (APS) and the oxidant ferric chloride (FeCl3) were added. The molar ratio of the initiator ammonium persulfate to the monomer 3,4-ethylenedioxythiophene was 1.17:1, and the molar ratio of the oxidant ferric chloride to the monomer 3,4-ethylenedioxythiophene was 0.01:1. The mixture was stirred gently in an ice-water bath to allow EDOT to fully polymerize until the reaction was complete, and finally a HEC-anchored conductive polymer (PEDOT:PSS@HEC) dispersion was obtained.

[0033] (2) Preparation of acrylamide prepolymer solution and conductive hydrogel preparation: A low-temperature prepolymerization method was used to form an acrylamide (AM) prepolymer network. AM was dissolved in water to obtain a solution with a mass fraction of 30 wt%. Subsequently, the initiator ammonium persulfate and the crosslinker N,N'-methylenebisacrylamide were added. The addition amount of crosslinker N,N'-methylenebisacrylamide and initiator ammonium persulfate was 0.17 wt% and 0.15 wt% of the mass of AM monomer, respectively. The reaction was carried out at room temperature for 1 h to form a prepolymer solution with adjustable crosslinking density. The HEC-anchored conductive polymer dispersion was mixed with the AM prepolymer solution in a volume ratio of 1:7. The two-phase uniform dispersion was achieved by vortex mixing and ultrasonic treatment. The mixed system was added to a homemade hydrogel mold and thermally initiated polymerization at a temperature of 70 ° C for a reaction time of 2 h to finally form a covalently crosslinked polyacrylamide (PAM) network. At the same time, the physically crosslinked composite conductive polymer network was uniformly embedded in it, namely the double network hydrogel (PEDOT:PSS@HEC / PAM). Figure 2 、 Figure 3 This indicates that the conductive polymer obtained by using 1.5 wt % HEC as a biological template in Example 2 has poor uniformity and dispersibility, and the mechanical properties of the hydrogel prepared based on this conductive polymer are inferior to those of the hydrogel in Example 1.

[0034] (3) Hydrogel encapsulation and sensing performance testing: The prepared hydrogel was cut into appropriate sizes and encapsulated with VHB transparent tape to ensure that the hydrogel was isolated from the external environment. The encapsulated hydrogel was used as a sensing element and connected to a signal acquisition system. Its resistance change under different strains was tested to evaluate its sensing performance.

[0035] Comparative Example 1

[0036] A method for preparing a two-stage polyacrylamide hydrogel based on low-temperature prepolymerization and thermal initiation polymerization comprises the following steps:

[0037] (1) Preparation of acrylamide prepolymer solution and preparation of hydrogel: A low-temperature prepolymerization method was used to form a prepolymer network of acrylamide (AM). AM was dissolved in water to obtain a solution with a mass fraction of 30 wt%, and then the initiator ammonium persulfate and the crosslinker N, N'-methylenebisacrylamide were added. The addition amount of crosslinker N, N'-methylenebisacrylamide and initiator ammonium persulfate were 0.17 wt% and 0.15 wt% of the mass of AM monomer, respectively. The reaction was carried out at room temperature for 1 hour to form a prepolymer solution with adjustable crosslinking density, which was then stored in a refrigerator to stabilize it for a period of time. The prepolymer solution was mixed with water in a volume ratio of 7:1, and the bubbles were removed by ultrasound. Then, the solution was added to a homemade hydrogel mold and thermally initiated polymerization at a temperature of 70 ° C and a reaction time of 2 hours to finally form a covalently crosslinked polyacrylamide (PAM) network. By Figure 2 It was observed that the mechanical properties of the hydrogel prepared in Comparative Example 1 were significantly different from those in Examples 1 and 2.

[0038] (2) Hydrogel encapsulation and sensing performance testing: The prepared hydrogel was cut into appropriate sizes and encapsulated with VHB transparent tape to ensure that the hydrogel was isolated from the external environment. The encapsulated hydrogel was used as a sensing element and connected to a signal acquisition system. Its resistance change under different strains was tested to evaluate its sensing performance.

[0039] Comparative Example 2

[0040] A method for preparing a composite hydrogel based on a synergistically enhanced double network of a conductive polymer and polyacrylamide comprises the following steps:

[0041] (1) Preparation of conductive polymer dispersion: polystyrene sulfonic acid (PSS) was dissolved in water, and 3,4-ethylenedioxythiophene (EDOT) monomer was slowly added to the solution, and ultrasonic dispersion was performed to form a homogeneous mixed solution. The mass ratio of EDOT to PSS in the mixed solution was 1:2.5, and the total mass fraction of the two was 1.5wt% of the mixed solution; the pH value of the system was adjusted to 2 with sulfuric acid, and then the initiator ammonium persulfate (APS) and the oxidant ferric chloride (FeCl3) were added. The molar ratio of the initiator ammonium persulfate to the monomer 3,4-ethylenedioxythiophene was 1.17:1, and the molar ratio of the oxidant ferric chloride to the monomer 3,4-ethylenedioxythiophene was 0.01:1; the mixture was stirred gently in an ice-water bath to allow EDOT to fully polymerize until the reaction was complete, and finally a dispersion of conductive polymer PEDOT:PSS was obtained.

[0042] (2) Preparation of acrylamide prepolymer solution and preparation of conductive hydrogel: A low-temperature prepolymerization method was used to form an acrylamide (AM) prepolymer network. AM was dissolved in water to obtain a solution with a mass fraction of 30 wt%. Subsequently, the initiator ammonium persulfate and the crosslinker N,N'-methylenebisacrylamide were added. The addition amount of crosslinker N,N'-methylenebisacrylamide and initiator ammonium persulfate was 0.17 wt% and 0.15 wt% of the mass of AM monomer, respectively. The reaction was carried out at room temperature for 1 h to form a prepolymer solution with adjustable crosslinking density. The conductive polymer dispersion and the AM prepolymer solution were mixed in a volume ratio of 1:7, and the two-phase uniform dispersion was achieved by vortex mixing and ultrasonic treatment. The mixed system was added to a homemade hydrogel mold and thermally initiated polymerization at a temperature of 70 ° C for a reaction time of 2 h to finally form a covalently crosslinked polyacrylamide (PAM) network. At the same time, the physically crosslinked conductive polymer network was uniformly embedded in it, i.e., a double-network hydrogel. Figure 3 It shows that the uniformity of the conductive polymer prepared in Comparative Example 2 is slightly worse than that in Example 1, but better than that in Example 2.

[0043] (3) Hydrogel encapsulation and sensing performance testing: The prepared hydrogel was cut into appropriate sizes and encapsulated with VHB transparent tape to ensure that the hydrogel was isolated from the external environment. The encapsulated hydrogel was used as a sensing element and connected to a signal acquisition system. Its resistance change under different strains was tested to evaluate its sensing performance.

[0044] Application Example 1 Mechanical Tensile Stress / Strain Sensing Application

[0045] Cut the prepared hydrogel into appropriate sizes and seal it with VHB transparent tape to ensure that the hydrogel is isolated from the external environment. Figure 4As shown in Figure a, it is similar to a sandwich structure. The encapsulated hydrogel is fixed on a mechanical tensile testing machine, and both ends are connected to the electrodes of the LCR digital source meter signal acquisition system. Apply different tensile strains to the hydrogel and record its resistance change. Analyze the relationship between resistance change and strain to evaluate the sensitivity and response speed of the hydrogel. Repeat the test many times to evaluate the stability and repeatability of the hydrogel. Figure 4 As shown in Figure b, there is a linear correlation between the relative change in hydrogel resistance (ΔR / R0) and the tensile strain, and ΔR / R0 shows a monotonically increasing trend with the increase in tensile strain. Specifically, this linear relationship can be roughly divided into three stages: in the initial stage (strain range 0%-50%), the sensitivity factor (GF1) is 1.58, the determination coefficient (R1 2 ) is 0.991; in the second stage (strain range 50%-100%), GF2 is 2.85, R2 2 is 0.999; in the third stage (strain range 100%-900%), GF3 reaches 7.35, R3 2 is 0.996, indicating a significant linear correlation. This indicates that the conductive hydrogel can provide accurate resistance signal feedback under different strain amplitudes. In addition, Figure 4 Figures c and d show the resistance changes of the hydrogel during four loading-unloading cycles at small strains (20%, 40%, 60%, 80%, and 100%) and three loading-unloading cycles at large strains (100%, 200%, 300%, 400%, 500%, and 600%), respectively. This shows that the flexible sensing material based on PEDOT:PSS@HEC / PAM can accurately respond to various strain states and stably identify and output the same type of signal over a long period of time. This shows that the material has the accuracy and stability to screen feedback signals. Figure 5 Figure (a) shows the sensor's response time under two conditions: rapid force application and release; and application and hold followed by release. In the rapid force application and release test, the response time was approximately 55ms, with a recovery time of approximately 660ms. In the test where force was applied and held followed by release, the response time was approximately 150ms, with a recovery time of approximately 890ms. This demonstrates the hydrogel's high signal sensing capabilities. Figure 5 Figure b shows the stretch-recovery cycle performance of the hydrogel under fixed strain conditions, indicating that the hydrogel has good fatigue resistance. In summary, the PEDOT:PSS@HEC / PAM conductive hydrogel exhibits high sensitivity, excellent linearity, fast response time, and a wide response range, which ensure its excellent performance and accuracy in sensing applications.

[0046] Application Example 2: Human Activity and Physiological Activity Sensing Application

[0047] The prepared hydrogel is cut into appropriate sizes and encapsulated with VHB transparent tape to ensure that the hydrogel is isolated from the external environment and that the encapsulated sensor can fit well with human skin. The encapsulated hydrogel sensor is attached to the wrist joint, finger joint, knee joint, throat, brow, pulse, arm and other parts of the human body to detect the signals of human activity and electrocardiogram / electromyography signals. At the same time, the sensor is connected to the electrodes of the LCR digital source meter signal acquisition system to record the resistance changes of the hydrogel during human activity. By having the subjects perform a series of movements (such as wrist bending, finger flexion and extension, knee bending, pronunciation, frowning, swallowing, etc.), the resistance changes of the hydrogel sensor in different motion states are recorded, such as Figure 6 As shown in Figures a through f, the sensor clearly records changes in signal peaks as the fingers switch between different bending angles (f). During wrist and knee bending, the electrical signal exhibits distinct regularity. The "signature signal" induced by vocal cord vibration during the syllable "yes" is also accurately captured (c). Figure 7 As shown in Figure 2, the sensing device based on the PEDOT:PSS@HEC / PAM hydrogel bioelectrode can provide timely and accurate electrical signal responses to human electrocardiogram and electromyography signals, respectively. Figure 7 Figures a and b show this. In the magnified images, characteristic peaks such as the P wave, QRS complex, and T wave are clearly visible. Repeated muscle stimulation in the electromyographic signal further confirms the accuracy and stability of the hydrogel-based bioelectrode. This demonstrates the hydrogel sensor's ability to provide rapid, real-time feedback, ensuring efficient and convenient detection. The clear distinction between the different signals reflects the hydrogel sensor's precise feedback capabilities and its wide detection range, enabling it to collect a variety of signal variations under common deformation levels.

[0048] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions or improvements made within the spirit and principles of the present invention should be included in the scope of protection of the present invention.

Claims

1. A method for preparing a composite hydrogel based on biological template induction and dual network synergistic enhancement, characterized by: The following steps are involved: Dissolving hydroxyethyl cellulose in a solvent to obtain a homogeneous solution; adding 3,4-ethylenedioxythiophene and polystyrene sulfonic acid to the dissolving solution and carrying out a polymerization reaction to obtain a dispersion containing a composite conductive polymer; An acrylamide prepolymer solution is prepared, the acrylamide prepolymer solution and a dispersion solution containing a composite conductive polymer are uniformly mixed, and a target product is obtained by thermally initiating free radical polymerization.

2. The method for preparing a composite hydrogel based on biological template induction and double network synergistic enhancement according to claim 1, characterized in that: The mass fraction of hydroxyethyl cellulose in the dissolving solution is 0.25 wt % to 1.5 wt %.

3. The method for preparing a composite hydrogel based on biological template induction and double network synergistic enhancement according to claim 1, characterized in that: The method for carrying out the polymerization reaction is: after adding 3,4-ethylenedioxythiophene and polystyrene sulfonic acid to the dissolution solution, the pH value of the system is adjusted to acidic by sulfuric acid, the temperature of the system is controlled by an ice water bath, and then an initiator and an oxidant are added to start the polymerization reaction and finally obtain a dispersion of the composite conductive polymer.

4. The method for preparing a composite hydrogel based on biological template induction and double network synergistic enhancement according to claim 3, characterized in that: The initiator is ammonium persulfate.

5. The method for preparing a composite hydrogel based on biological template induction and double network synergistic enhancement according to claim 3, characterized in that: The oxidant is ferric chloride.

6. The method for preparing a composite hydrogel based on biological template induction and double network synergistic enhancement according to claim 1, characterized in that: The method for preparing the acrylamide prepolymer solution comprises: dissolving acrylamide monomer in water, adding an initiator and a cross-linking agent in sequence, and reacting at room temperature to obtain the acrylamide prepolymer solution.

7. The method for preparing a composite hydrogel based on biological template induction and dual network synergistic enhancement according to claim 6, characterized in that: The initiator is ammonium persulfate.

8. The method for preparing a composite hydrogel based on biological template induction and dual network synergistic enhancement according to claim 6, characterized in that: The cross-linking agent is N,N'-methylenebisacrylamide.

9. A composite hydrogel based on bio-template induction and dual network synergistic enhancement, characterized by: The invention discloses a novel novel nanostructured carbonyl phosphate ...

10. Use of the composite hydrogel based on biological template induction and double network synergistic enhancement as claimed in claim 9 in flexible sensors.